SPECTROPHOTOMETRIC DIAGNOSIS OF DERMATOSCOPIC IMAGES OF PIGMENTED SKIN TUMORS - Galaychuk, I. Y.; Hotsko, O. S.; Danylchuk, Y. R. (Вісник наукових досліджень, 2015)
The method of diagnosis of pigmented skin tumors using spectrophotometric analysis (SPM) of dermatoscopic images was analyzed in the article. The obtained results indicate the possibility of using SPM as an addition to the standard methods of dermatoscopic diagnostics to make the correct diagnosis that is confirmed by clinical examples and are histologically proven.